2016
DOI: 10.1002/ejic.201600959
|View full text |Cite
|
Sign up to set email alerts
|

Well‐Dispersed Fe2O3 Nanoparticles on g‐C3N4 for Efficient and Stable Photo‐Fenton Photocatalysis under Visible‐Light Irradiation

Abstract: In this study, a highly efficient heterogeneous photo‐Fenton system (Fe2O3/g‐C3N4/H2O2/visible light) has been developed. The heterogeneous catalyst Fe2O3/g‐C3N4 in this system was successfully prepared by growing Fe2O3 nanoparticles on the surface of g‐C3N4. The Fe2O3 nanoparticles could achieve high dispersion on the surface of g‐C3N4 and form a heterojunction with g‐C3N4 to improve the charge separation. In addition, the combination of the Fenton's reagent Fe2O3/H2O2 and the photocatalyst g‐C3N4 greatly enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…The peaks in bottom line at 24.1°, 33.1°, 35.7°, 40.9°, 49.5°, 54.1°, 62.5° and 64.0° can be assigned to (012), (104), (110), (113), (024), (116), (214) and (300) lattice planes of α−Fe 2 O 3 (JCPDF No. 33‐0664), indicating that the MIL‐101 (Fe) has been oxidized to α−Fe 2 O 3 with high purity during calcination process . The uppermost line displays two typical peaks at 12.9° and 27.6° related to (100) and (002) lattice planes of g−C 3 N 4 , meaning that the calcination product of melamine is g−C 3 N 4 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The peaks in bottom line at 24.1°, 33.1°, 35.7°, 40.9°, 49.5°, 54.1°, 62.5° and 64.0° can be assigned to (012), (104), (110), (113), (024), (116), (214) and (300) lattice planes of α−Fe 2 O 3 (JCPDF No. 33‐0664), indicating that the MIL‐101 (Fe) has been oxidized to α−Fe 2 O 3 with high purity during calcination process . The uppermost line displays two typical peaks at 12.9° and 27.6° related to (100) and (002) lattice planes of g−C 3 N 4 , meaning that the calcination product of melamine is g−C 3 N 4 .…”
Section: Resultsmentioning
confidence: 97%
“…Nevertheless, the short lifetime of photo‐generated charge carriers and small hole diffusion length greatly hinder the widespread application of α−Fe 2 O 3 in photocatalysis . In the past several years, the coupling of g−C 3 N 4 with α−Fe 2 O 3 has been an effective route to enhance themselves′ visible‐light photocatalytic activity in various fields such as pollutant degradation, hydrogen production, CO 2 reduction, organic synthesis, and nitrogen fixation . Due to the appropriate band positions of α−Fe 2 O 3 and g−C 3 N 4 , the strong interfacial coupling of α−Fe 2 O 3 /g−C 3 N 4 hybrids largely promoted the transfer and separation of photoinduced charge carriers by common or even Z‐scheme modes, directly accounting for their high photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced oxidation process such as the Fenton reaction and photocatalysis has been extensively studied due to their high degradation activity toward the refractory organic pollutants in recent years [1]. The Fenton reaction has been proven to mineralize most of the organic pollutants [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, the g-C 3 N 4 has many weak points such as the small surface area, high recombination rate of photogenerated electron-hole pairs and low visible light utilization efficiency. 15 Hence, various methods have been used to solve these problems, for example, synthesizing different structures, 16,17 doping with metal or nonmetal elements, [18][19][20][21] coupling with other semiconductors, [22][23][24][25][26] and modifying by conjugated polymers. 27,28 Among these methods, the conjugated polymer modication has attracted many attentions because the conjugated polymer not only can enhance the absorption of the visible light but also can act as a semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al synthesized carbon nitride-poly(3-hexylthiophene) (g-C 3 N 4 -P 3 HT) composite photocatalyst. 24 They found that the novel photocatalyst exhibited signicantly enhanced photocatalytic activity. Thakare et al reported on the synthesis of a ternary polymer composite of graphene, carbon nitride, and poly(3-hexylthiophene) (G-g-C 3 N 4 -P 3 HT) which had enhanced photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%